2021
DOI: 10.1021/acs.est.0c08150
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated Polycyclic Aromatic Hydrocarbons and Arachidonic Acid Metabolisms Relevant to Cardiovascular Pathophysiology: Findings from a Panel Study in Healthy Adults

Abstract: Concerns on nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) in the environment have mainly arisen from their mutagenic and carcinogenic effects. The objective of this study is to investigate whether nitro-PAH exposures are associated with biomarkers of cardiovascular pathophysiology. In a panel study design, urines and blood samples were collected up to four times with a 2-week interval from 89 healthy adults. We measured 1-naphthylamine, 2-naphthylamine, 9-aminophenanthrene, 2-aminofluorene, and 1-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Remarkably, we found that disease status (i.e., COPD and IHD) is significantly associated with increased urinary APAH levels. This is mechanistically supported by our recent panel studies that associated urinary APAH levels with biomarkers relevant to cardiovascular pathophysiology . Considering the exploratory nature of these findings, future efforts are needed to further clarify the cardiopulmonary effects associated with urinary APAH levels.…”
Section: Discussionmentioning
confidence: 53%
“…Remarkably, we found that disease status (i.e., COPD and IHD) is significantly associated with increased urinary APAH levels. This is mechanistically supported by our recent panel studies that associated urinary APAH levels with biomarkers relevant to cardiovascular pathophysiology . Considering the exploratory nature of these findings, future efforts are needed to further clarify the cardiopulmonary effects associated with urinary APAH levels.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, we found that 11 upregulated genes ( cox2 , cox5b2 , cox6a1 , cox6b2 , cox6c , cox7a , cox7a2a , cox7c , cox8b , uqcrq , and uqcrh ) enriched in these three signaling pathways (cardiac muscle contraction, metabolic pathways, and oxidative phosphorylation pathway) (Figure A,C), are the cyclooxygenase (COX) subunits. A recent study reported that exposure to nitro-PAHs may increase oxidative stress, change the activity of the COX family, and adversely affect cardiovascular health . We found that DCBQ upregulated 7 genes ( al929536.3 , gstm.1 , gstm.3 , gsto2 , gstp1 , gstr , and gstt1b ) enriched in three signaling pathways: metabolic pathways, xenobiotics metabolism (cytochrome P450), and glutathione metabolism.…”
Section: Resultsmentioning
confidence: 67%
“…A recent study reported that exposure to nitro-PAHs may increase oxidative stress, change the activity of the COX family, and adversely affect cardiovascular health. 59 We found that DCBQ upregulated 7 genes (al929536. 3, gstm.1, gstm.3, gsto2, gstp1, gstr, andgstt1b) enriched in three signaling pathways: metabolic pathways, xenobiotics metabolism (cytochrome P450), and glutathione metabolism.…”
Section: Dcbq Elicited Responses Of Respiratory Electron Transport Ch...mentioning
confidence: 79%
“…PAHs are important components of atmospheric aerosols, which are mostly concentrated in fine particles ( Li et al, 2016 ; He et al, 2018 ). Urinary PAHs are frequently used to estimate total exposure to PAHs ( He et al, 2021 ). Previous studies have shown that the concentration of PAHs in the air of China is high inland and low along the coast ( Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%